(3efGOM GdeeGOM hQhVI GdeBKQ hGdeaGNQ aj NUGFU Gdedc GdfGUQs - (3YHO GdefYe GdLdjGfj , YHO GdefYe Hf YeQ Hf MSGf GdZSGfj GdCfOdSj, CHh GdaVd,J (B602 (3g` s
(3ChdgG (B:s
(3hGYde Cf CHjGJ gPg GdeOHLI GdeTLQI HSGbgG GdJi jSdc ai hSW GdeOHLI WhdkG s
(3BNQgG (B:s
(3Mei GdeSLO GdCbUi aXd eWgQkG hChOYg LeYkG cHGQkG QLGdg cedJ GdeOHLI PGJ GdCfgGQ GdCQHYI HYhf Gddg s
(3ajgG eG cJH HGddhf GdCMeQ hGdCNVQs
(3hgj bUGFO oeOHLI fXegG ai eOM UdGM GdOjf jhSa GdCjhHis
(3ai aJM GdbOS YLjHg ai CSdhHgG hJTLjQgG hLOGhdgG hJQJjHgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs